Attention deficit hyperactivity disorder symptoms among medical students at the University of Belgrade: Detection and association with sociodemographic characteristics, academic achievements and loneliness - Kojović Natalija; Joković Nikola; Mandić-Maravić Vanja; Marić Nađa P. (Medicinski Podmladak)
Introduction: Attention deficit hyperactivity disorder (ADHD) is a psychiatric disorder with a typical childhood onset. Mental disorders, social difficulties and dysfunctionality are maintained in adulthood, but they can also be resolved. To detect ADHD symptoms in the adult population, appropriate instruments have been developed and they haven't yet been applied to students in Serbia. Aim: To find the prevalence of positive detection of ADHD symptoms among medical students and the association with sociodemographic characteristics, academic achievements and loneliness. Material and methods: A cross-sectional study was conducted at the University of Belgrade Faculty of Medicine by distributing a questionnaire online. In the first part of the questionnaire, data on the socio-demographic and academic characteristics were collected. To detect ADHD symptoms in adults, assess the personal perception of social status, and evaluate loneliness, the ASRS-v1.1, Scale of Subjective Social Status, and Hughes' Loneliness Scale were used, which comprised the second part of the questionnaire. Data analysis involved descriptive and analytical statistical methods. Results: The sample consisted of n = 404 students of all years of the university (age 18-30 years). A total of 21.7% of the students had positive detection of ADHD symptoms. Among those with positive detection, the average academic grade was 8.5 ± 0.8, while in the negative group, it was 8.7 ± 0.7 (p = 0.009). Students with a positive detection were lonelier (p < 0.001). The following symptoms had the highest predictive power for a positive detection: difficulty paying attention when doing a boring task, trouble concentrating during conversations/ interactions with people, difficulty finding things, or losing them, and excessive socializing. Conclusion: This study provides an initial insight into the prevalence of ADHD symptoms in a convenience sample of the student population at the University of Belgrade. The presented results help to identify and better understand the difficulties faced by some students and to seek appropriate methods to alleviate their condition.